Nilai Keislaman Dalam Tradisi 'Kenduren' Bagi Masyarakat Wonosalam Kabupaten Jombang - risda sufidiana; Izzatin Nisa'; Masyhuri Masyhuri (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2021)
Religion is a symbol of the value of obedience to the God. Culture also contains value and symbol so that humans can live in. According to Ahlusunnah Wal-jama'ah, the values of tradition and cultural is a character that have social attitudes in culture (socio-cultural); Tawassuth (moderate), Tasamuh (tolerant), and Tawazun (harmony). 'Kenduren’ is an annual tradition to express gratitude for blessing of the Bido Durians’ harvest in Wonosalam, Jombang. This study used descriptive qualitative research method and three approaches; data approach, the researcher perspective approach, and theoretical approach. It is found that the attitudes of Tawassuth, Tasamuh, and Tawazun are implemented in the tradition of 'Kenduren'. The indicators are all the people are welcome, respecting each other for the people who conducted grave pilgrimages, a good relationship between the government and the people in respecting the issues of status, position or group, that all of them are in the corridor of maqasid al-shariah.